Frecuencia de riego en el comportamiento vegetativo en Lactuca sativa L. en el sistema hidropónico NFT, Loreto-2021 - Sanchez Garcia, Angelica Patriana (2023)
Lettuce is one of the vegetables that thrives adequately in a hydroponic system, it is developed under protective agriculture, the main objective was to determine the effect of irrigation frequency on the vegetative behavior of lettuce, the frequencies were every 1 hour (T1 ), every 2 hours (T2), every 3 hours (T3) and every 4 hours (T4). The Unrestrictedly Random Design with 30 repetitions was used. The results show significant statistical difference (p<0.01) of irrigation frequency every 1h in all the frequencies for the total weight of the plant with 32.33 g, likewise every 2h and every 3h are shown in the same group, these being significant for every 4h. Growing lettuce with an irrigation frequency every 1 hour, better productivity is obtained in the number of leaves and in the total weight of the plant in the technique of laminar flow of nutrients managed in the hydroponic system under the climatic conditions of the Loreto region.